Study of the factors affecting Anemia in pregnant women in Al-Damer region, Sudan - Abdel Hafeez, Manal Mohamed; Elhidai, Marim Mohammed; Al- Tayeb, Zainab Al- Zubair; Ali, Dawla Ali Adam (Journal of agricultural, environmental and veterinary sciences, 2020)
Objectives: The study aims to formulate and measure the effect of a dietary counseling program for pregnant women with anemia in the Damer region. The importance of the research lies in the fact that many studies and studies have confirmed the prevalence of iron deficiency anemia among women of childbearing age and during pregnancy. Iron anemia usually has a deficiency in other elements such as folic acid, vitamin A and vitamin B complex. The deficiency of these elements has a negative impact on the weight of the newborn and on the health of the pregnant woman, On the other hand, the causes of any anemia were their type, ignorance- poverty- poor eating habits. Procedures: The study was conducted in Damer Hospital and seven health centers in the Damer area, River Nile State. The sample included 30 pregnant women with anemia and frequenting health centers and Damer Hospital during the study period. Where the study was carried out in the second period of pregnancy (14- 25) weeks, for the tribal questionnaire, and pregnant women in the third period of pregnancy (26- 37) weeks, for the post- questionnaire, where the proposed diet program was presented and explained by the researcher for the sample, It is a total of eight informational messages for pregnant women with anemia in the Damer region. Then measure the effect on the post-trial experience in the third trimester of pregnancy (26- 37) weeks. Also providing local food rich in iron for the sample, then measuring its effect after 6 weeks (20- 31) weeks. The main purpose of providing these meals is to raise cognitive food awareness and to measure awareness and knowledge of the nutritional content of the local materials provided. Results: The results of the study showed a low level of education, as the level of education of most of the sample’s members is essential, (43.3%) of the sample. And the number of their children was (1- 3), (46.7%), in the age group of (20- 29) years, which indicates the multiplicity of births. The results of the study also showed the prevalence of early marriage, and the age group for marriage was (15- 19) years, (70%) of the study sample. The results of the study also showed the weakness of nutritional knowledge in the sample (food illiteracy), by (80%) of the study sample. Prevalence of anemia (iron deficiency), with three levels, mild anemia (9.5- 10.4 g / dl), moderate anemia (8.5- 9.4 g / dl), severe anemia (7.5- 8.4 g / dl) by 30% and 46%..7% and 23.3%, respectively. The study also showed the lack of a good choice for the types of foods that can increase hemoglobin, that is, lack of knowledge of iron-rich substances (60.0%). The results of the study showed an increase in the level of nutritional and cognitive awareness, an increase in the level of hemoglobin, a decrease in the rates of anemia, an increase in awareness of the importance of monthly follow- up to the doctor, and knowledge and selection of iron-rich foods that increase hemoglobin in the blood. Among the recommendations of the study are designing programs to raise nutritional and health awareness in the region, focusing on the correct healthy food habits and moving away from incorrect food habits, using the local food and nutritional resources available in the study area, and conducting more research in the field of designing food and nutritional education programs. Training of cadres working in the field of nutritional health education, providing audio and visual guidance tools in the field of nutritional education in health centers of childbearing age, And encourage the cultivation of some vegetables at home, such as watercress, purslane and spinach.